Fundamental study about lighting photographic imagery: exploring new theory for digital post-production methodology - Ismail, Adzrool Idzwan (2011)
Light, is a basic element yet is extremely important in Photography. The importance of light is as important as human needs a soul that lives within their body. Without soul, how can one live in this adventurous and wonderful life? Without light, an image can never be recorded and witnessed by people. For a Photographer or Image Maker, light is the main priority that add up variety of colours and flavours in photographs. It has the ability to help the creation of good and quality images and grabbing people attention. According to Sir John F.W. Herschel (1839), the words photography itself derived from Greek language, that is; 'photo' means 'light' and 'graphein' means 'to draw'. This clearly informed us that once upon a time, the definition of photography is drawing with light. Technically, in photography, the creation of a quality image depending on several most important aspect. One of the aspect that can be described here is International Standard Organization (ISO) that used by a photographer for his or her images. [what is ISO?]. Besides that, resolution is also running in the contribution high quality images. The resolution of images is controlled by the amounts of pixels available in a camera systems that affecting the images sizes and clarity. In this research, the researcher will focused towards the amounts in different levels and types of lights that go through the camera mechanism to initiate the process of drawing with light or better known as "image recording".